Community-based adaptation: an approach to build resilience and sustainable development in West Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security; CARE; ENDA (2013)
Participants from 12 West African countries confirmed the urgent need for community based adaptation to respond to the adverse effects of climate change at a West Africa Learning Event in Cotonou, 3-6th September 2013. 72 participants from a diverse range of 36 NGO and research organisations and 14 government organisations shared and reflected on their experiences, successes, challenges, opportunities, questions and future perspectives across the region. This communiqué is the collective product of these deliberations conveying strong messages on the crucial need to develop effective adaptation practice and policies to secure livelihoods and realise resilient development and economic growth in the face of an uncertain and changing climate.